A decision heuristic for party identification : new British and German data and a new understanding for a classic concept - Alan S. Zuckerman; Malcolm Brynin (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
The concept party identification lies at the heart of much research on political preferences and behavior in established democracies. Drawing on data obtained from the British Household Panel Survey (1991-99) and the German Socio-Economic Panel Survey (1984-1998), we offer a fresh approach to the concept. Party identification is a stance that people take towards the political parties. They apply a consistent rule -a decision heuristic -persistently returning to the same preference year after year or behaving haphazardly, moving with no clear pattern among the choices. Most take a definitively negative stance towards one of the parties and a positive stance towards the other major party. Of these, about half display behavior that reflects a psychological commitment and about half are as likely as not to pick that party when asked. For most people, party identification is neither a loyalty, as conceived by traditional understanding associated with the Michigan -nor a calculated choice -as offered by rational choice theory -but a way to situate oneself persistently in relation to the relatively distant objects of politics.
Keywords: 330; Party Identification; decision heuristic; panel surveys; British and German politics; Wahlverhalten; Politische Partei; Entscheidung; Heuristisches Verfahren; Großbritannien; Deutschland